Barriers and facilitators faced by individuals with intellectual disabilities and/or autism when accessing primary healthcare: a commentary of a systematic review. (2nd December 2022) - Poole, Chloe; Hill, James; Harrison, Joanna; Doherty, Alison
Abstract : Individuals with intellectual disability and/or autism spectrum disorder experience healthcare inequalities and have more unmet healthcare needs than the general population. Despite this, there is a sparsity of literature exploring the views of individuals with autism spectrum disorder and/or intellectual disability. This article summarises and evaluates an integrated review that explores the barriers and facilitators those with intellectual disability and/or autism spectrum disorder face when accessing primary healthcare.